Increased CD3 positive cells in bronchoalveolar lavage fluid after hydrogen fluoride inhalation - Lund, K.; Refsnes, Magne; Sandstrøm, T.; Søstrand, P.; Schwarze, P.; Boe, J.; Kongerud, Johny (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'This study examined whether experimental hydrogen fluoride exposure for 1 hour induces an inflammatory response in the lower respiratory tract that is detectable in bronchoalveolar lavage fluid. Methods Nineteen healthy, nonsmoking men were exposed for 1 hour to constant according to low (£0.6 mg/m3), intermediate (0.7-2.4 mg/m3), or high (2.5-5.2 mg/m3) concentrations of hydrogen fluoride. Bronchoalveolar lavage was performed at least 3 weeks before and 24 hours after the exposure. For 15 subjects differential countings were performed. Results There was a significant increase in the percentage of CD3 positive cells in the bronchial portion for those exposed to "intermediate" and "high" concentrations. For the "high" exposure group the increase in the bronchoalveolar portion was also significant. A significant correlation was found between the increase in the percentage of lymphocytes and CD3 positive cells in the bronchoalveolar portion (Spearman's coefficient r=0.68, P=0.008). Myeloperoxidase and IL-6 increased significantly in the bronchial portion for those exposed to "high" concentrations. There was a significant increase in myeloperoxidase (P=0.005) for all exposures, while there was a decrease in E-selectin (P=0.007). Conclusions Hydrogen fluoride may induce an inflammatory reaction in the airways at concentrations that can occur in the ambient air in the primary aluminum industry.
Keywords: bronchoalveolar lavage; fluorides; inflammation